Analisis kebiasaan Baik dalam Implementasi Profil Pelajar Pancasila SDN Gayamsari 02 Semarang - Gusfan Ristiyanto; Intan Indiati; Loli Gunawan Adi; Mudzanatun Mudzanatun (Program Pascasarjana UNU Surakarta, 2023)
Character education can be carried out from an early age through elementary school, which is the foundation for the formation of superior character in accordance with Pancasila and implementing lifelong learning. Character is very significant in the perspective, way of thinking, and acting of each individual (Lubaba, 2022). Behavioral deviations often occur in the environment around us, including those committed by elementary school students who do not reflect the practice of Pancasila in good habits that have been programmed and applied at school every day. The inter-accessive analysis step in the Qualitative method is used to analyze the results of observations and interviews (B. Matthew Milles & Michael Huberman, 1992). The research place is SDN Gayamsari 02 Semarang with the research subjects of teachers and students of class IV B SDN Gayamsari 02 Semarang. Qualitative data collection techniques according to (Sugiyono, 2013: 337 Faiz & Soleh, 2021) consist of data reduction, data presentation, and conclusion drawing. The analysis showed that SDN Gayamsari 02 Semarang has implemented good habituation practices based on the Pancasila learner profile starting from aspects of faith, devotion to God, and noble character to creative aspects. The application of the Pancasila learner profile is real and implemented when inside and outside of learning. Based on the results of the study, it can be concluded that the application of good habits in the implementation of the Pancasila learner profile of SDN Gayamsari 02 Semarang has been good, and is sustainable by applying fun methods that make it easier for students to implement noble moral values.